A peak position comparison method for high-speed quantitative Laue microdiffraction data processing. (15th January 2018) - Kou, Jiawei; Chen, Kai; Tamura, Nobumichi
Abstract: Indexing Laue patterns of a synchrotron microdiffraction scan can take as much as ten times longer than collecting the data, impeding efficient structural analysis using this technique. Here a novel strategy is developed. By comparing the peak positions of adjacent Laue patterns and checking the intensity sequence, grain and phase boundaries are identified, requiring only a limited number of indexing steps for each individual grain. Using this protocol, the Laue patterns can be indexed on the fly as they are taken. The validation of this method is demonstrated by analyzing the microstructure of a laser 3D printed multi-phase/multi-grain Ni-based superalloy. Graphical abstract: Image 2